Carotid baroreceptor reflex regulation of forearm vascular resistance in man. - Ebert, T J (1983)
The carotid baroreflex regulation of forearm vascular resistance in man is uncertain. Forearm vascular resistance, blood pressure and R-R interval responses to carotid sinus stimulation were therefore measured in seven healthy men. Carotid stimuli were delivered by gradually applying neck pressure, neck suction or neck suction during simultaneous low-level lower-body negative pressure. Mean arterial blood pressure and R-R interval responses to neck suction and pressure were immediate and were sustained throughout the periods of stimulation. In contrast, forearm vascular responses, were transient. During simultaneous mild lower-body negative pressure (which decreases cardiopulmonary baroreceptor stimulation and increases forearm vascular resistance), neck-suction-induced forearm vasodilation was exaggerated and sustained throughout the entire period of neck suction. There was a linear relationship between the level of resting forearm vascular resistance and the change in resistance produced by carotid stimuli. It is concluded that reflex changes in forearm vascular resistance provoked by carotid baroreceptor stimuli are immediate and evanescent in man. Simultaneous reduction of cardiopulmonary baroreceptor activity heightens the magnitude and duration of forearm vasodilation induced by carotid baroreceptor stimulation.